Factors related to the completeness of basic immunization for babies in Kadikadaran village, Ciruas health center working area in 2023 - Feling Polwandari; Noordina Septia Pascalisanty (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
The results of immunization completeness in Kadikaran Village, Working Area of ​​the Ciruas Health Center, are the lowest villages with respect to complete basic immunization completeness status of 52%. The purpose of this study was to determine the factors associated with the completeness of basic immunization in infants 0-9 months in Kadikaran Village, the working area of ​​the Ciruas Health Center. This type of research uses quantitative research with a correlation design using a cross sectional approach. The sample of this research is 84 respondents with total sampling method. The0results0of0the0study0showed0significant results,0namely p <0.05, there was a relationship between work 0.361, knowledge 0.000, self-efficacy 0.004, family support 0.002, support for health workers 0.005 and there was no relationship to the education variable 0.146 (p <0.05). The research hopes that health workers will provide alternative ways in the posyandu program for working mothers to keep their children immunized.